Inclusion in Education: Reconsidering Limits, Identifying Possibilities - Zgaga, Pavel (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2019)
This book seeks to offer a contribution to the ongoing discussion on inclusion in education. The initiative was born in a research group from the University of Ljubljana, Slovenia. Three researchers from Italy, Serbia and the United Kingdom joined the group later. The authors believe that the book offers relatively fresh perspectives on the topic. Firstly, the authors provide an interdisciplinary perspective by approaching the concept of inclusion on three horizons, which they understand as mutually compatible and co-dependent: pedagogical approaches, social contexts and theoretical reflections. Secondly, they offer a specific geographical perspective. The authors' desire is to highlight specific perspectives that are not common in the 'mainstream' literature: perspectives from Central and Southern Europe.